2020
DOI: 10.5713/ajas.19.0361
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of different enzymatic hydrolysates from desalted duck egg white

Abstract: Objective: The objective of this study was to look for optimal preparation of hydrolysates of desalted duck egg white powder (DDEWP) by the three different proteases and to investi gate their antioxidant and antimicrobial properties. Methods: DDEWP was hydrolyzed by three proteases, including pepsin (PEP), Bacillus spp. (BA) and natokinase (NAT) with three different enzyme concentrations (0.1%, 0.3%, and 0.5%), individually. The important key hydrolysis parameters such as hydrolysis degree, yield, antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results showed that the DH had a strong influence on the antioxidant activities of PPH. Thammasena and Liu [ 56 ] discovered that the DH correlated positively with the antioxidant capacity of desalted duck egg white hydrolysate.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the DH had a strong influence on the antioxidant activities of PPH. Thammasena and Liu [ 56 ] discovered that the DH correlated positively with the antioxidant capacity of desalted duck egg white hydrolysate.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of desalination by electrodialysis is that under the action of a direct current electric field, the ion exchange membrane selectively removes salts by anions and cations. The desalination efficiency of electrodialysis has reached more than 95%, but the energy consumption is relatively large, and the protein is easily denatured (Thamamsena, & Liu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of desalination by electrodialysis is that under the action of a direct current electric field, the ion exchange membrane selectively removes salts by anions and cations. The desalination efficiency of electrodialysis has reached more than 95%, but the energy consumption is relatively large, and the protein is easily denatured (Thamamsena, & Liu, 2019). The method of ion exchange resin is to use H‐type cation exchange resin to exchange various cations in water into H + , and use OH‐type anion exchange resin to exchange various anions in water into OH − , thereby removing or reducing salts in water.…”
Section: Introductionmentioning
confidence: 99%
“…This not only causes the waste of high-quality protein resources in the salted egg white, but also causes pollution to the environment and water sources due to the fermentation and decomposition products of the salted egg white exposed to the air. [11,12] Salted egg white is rich in protein and has similar nutritional value and ingredients to eggs. As we all know, egg white has a variety of biological activities, including antioxidant, anti-inflammatory, antibacterial, and anti-cancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…The pepsin hydrolysate of salted egg white was reported to have antioxidant and antibacterial activities, which can scavenge DPPH free radicals and inhibit Staphylococcus aureus. [12] Peptides from salted egg white can enhance osteoblast differentiation and anti-osteoporotic activity through the wnt/đ›œ-catenin signaling pathway and several key osteogenic transcription factors (such as Runx2 and OPG). [14] Therefore, the preparation of biologically active peptides from salted egg white is undoubtedly an important way for the high-value utilization of waste protein resources.…”
Section: Introductionmentioning
confidence: 99%